Normal Deviance: The Dreyfus Affair - Marie-Christine Leps (Cahiers Victoriens et Edouardiens)
This paper argues that the Dreyfus affair, as a national and then international discursive event, registers a general shift in power relations taking place at the turn of the century, from discipline to governmentality as the dominant mode for the exercise of power. Michel Foucault developed the notion of governmentality in his later works to grapple with the problematic of the government of self and others; he defined it as a form of power operating to foster the life of the one and the many, of each individual and of the population as a whole. Enmeshing issues of security and nation, of population and race, the Dreyfus affair forced governments, intellectuals, media, and what we now refer to as the ‘new social movements’ into wide-ranging debates and strategic interventions that forged new relations among them. Throughout, each group felt compelled to identify itself, to position itself in relation to this military trial turned political scandal: feminists, socialists, workers’ unions, anti-Semitic groups, revolutionary right-wing coalitions all needed to ‘come out,’ as it were, and in the process, the ever shifting norms of the acceptable and the deviant were redrawn. Perhaps more importantly, new modes of power and knowledge relations were being developed and normalized. Using the Dreyfus affair as a particularly telling case of a more general pattern, this paper presents an analytical model that could be transferred to different disciplinary inquiries; the play of power and resistance, the calculation of the normal and the deviant, and the determination of identity and subjectivity, are of particular importance.